INTRODUCTION TO ENGLISH POOR LAWS: 1349-1531 PERIOD A CHILD WELFARE PERSPECTIVE (Third Sector Social Economic Review, 2021)
This study examines the conditions, philosophies, socio-political and cultural context of English Poor Laws, and takes a critical look at the laws between 1349 and 1531. The study employs document analysis and purposeful sampling, interprets the data and findings by utilizing context and discourse analyses. Most of the poor laws are about prohibitions and restrictions on travel, labor, employment, and wages. They restrict wages and movements of poor, and the vocational education of their children. The first poor law of 1349-Statute of Labourers has been legislated as a response to the rapid demographic decline and socio-economic crisis caused by the pandemic in 1348. Lasting six hundred years, the Poor Law System has been abolished by the National Assistance Act in 1948. The poor laws condemn poor, treat them as irresponsible, idle vagabond, beggar, and enemy of the public, and punish them severely. The laws do not help poor with dignity, on the contrary, prohibit helping poor and victimize them. When help is available, here are some of the practices: Children, even five-six-year-old ones, are removed from their families, leased to businesses including mines for work so that the public expenses made for their grandparents and parents are covered. Some poor are sent to today’s USA as indentured servants with no pay. Close to 150 thousand poor children are sent overseas in the name of child protection. Poor children make up 50% of infamous workhouses. It is suggested that post-1531 poor laws are studied with similar critical lenses too.
Keywords: English Poor Laws; Child Welfare; Social Services